PEMBUATAN ALAT PERAGA MATEMATIKA DARI LIMBAH BAHAN ALAM DI DESA SIALOGO KABUPATEN TAPANULI SELATAN - Sormin, Masdelima Azizah; Lubis, Jumaita Nopriani; Batubara, Melvariani Syari; Dalimunthe, Lia Rosliana; Sakti, Bima; Manullang, Sakila (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2025)
Abstract: This Community Service (PKM) focuses on efforts to improve the quality of mathematics learning in Sialogo Village, South Tapanuli Regency, through the utilization of natural waste materials. The aim of this activity is to empower teachers and parents in creating affordable, creative, and contextual mathematics teaching aids by utilizing neglected local resources. The implementation method includes three main stages: (1) Identification and socialization, namely a needs survey and introduction to the concept of teaching aids from waste; (2) Training and mentoring, where participants are invited to directly design and make teaching aids such as "Fraction Boards from Areca Nut Trunks", "Counting Boards from Salak Seeds", and "Geoboards from Used Wood"; and (3) Implementation and evaluation, in the form of simulations of the use of teaching aids in the classroom and reflection discussions. The results of the activity showed a significant increase in participants' understanding of the importance of learning media. This was proven by the creation of 15 types of innovative teaching aids that could be directly applied. The enthusiasm of teachers and parents was very high, which was marked by their commitment to continue developing and using these teaching aids. This activity not only provides practical solutions to limited learning facilities but also instills environmental values and local wisdom through waste utilization.            Keywords: Teaching Aids, Natural Waste, Mathematics, Community Empowerment, Contextual Learning. Abstrak: Pengabdian kepada Masyarakat (PKM) ini berfokus pada upaya peningkatan kualitas pembelajaran matematika di Desa Sialogo, Kabupaten Tapanuli Selatan, melalui pemanfaatan limbah bahan alam. Tujuan dari kegiatan ini adalah untuk memberdayakan guru dan orang tua dalam menciptakan alat peraga matematika yang murah, kreatif, dan kontekstual dengan memanfaatkan sumber daya lokal yang terabaikan. Metode pelaksanaan meliputi tiga tahap utama: (1) Identifikasi dan sosialisasi, yaitu survey kebutuhan dan pengenalan konsep alat peraga dari limbah; (2) Pelatihan dan pendampingan, di mana peserta diajak secara langsung merancang dan membuat alat peraga seperti "Papan Pecahan dari Batang Pinang", "Papan Hitung dari Bijih Salak", dan "Geoboard dari Kayu Bekas"; serta (3) Implementasi dan evaluasi, berupa simulasi penggunaan alat peraga di kelas dan diskusi refleksi. Hasil kegiatan menunjukkan peningkatan yang signifikan dalam pemahaman peserta tentang pentingnya media pembelajaran. Terbukti dengan terciptanya 15 jenis alat peraga inovatif yang langsung dapat diaplikasikan. Antusiasme guru dan orang tua sangat tinggi, yang ditandai dengan komitmen mereka untuk terus mengembangkan dan menggunakan alat peraga tersebut. Kegiatan ini tidak hanya menyediakan solusi praktis untuk keterbatasan sarana belajar tetapi juga menanamkan nilai cinta lingkungan dan kearifan lokal melalui pemanfaatan limbah.Kata kunci: Alat Peraga, Limbah Alam, Matematika, Pemberdayaan Masyarakat, Pembelajaran Kontekstual.